PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Paranoan, Natalia; Tandirerung, Christina Jeane; Paranoan, Anthon (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study is aimed to test and analyze the effect of information technology usage and human resource competencies on the effectiveness of accounting information system. This study used primary data with survey method by distibuted questionnaires to employees of PT. X Makassar. The samples were defined by using purposive sampling method. This study distributed 50 questionnaires but only 45 questionnaires were returned and could be processed. Data that already collected were analyzed by multiple linear regression. The results show that information technology usage had positive and not significant effect to the effectiveness of accounting information system, and human resource competencies had positive and significant effect to the effectiveness of accounting information system. While information technology usage and human resource competencies simultaneous affect to the effectiveness of accounting information system.